KADAR AIR KRITIS PADA PROSES PENGERINGAN DALAM PEMBUATAN TEPUNG UBI JALAR (Ipomoea batatas (L) Lam.) - Niluh Sri Suryaningsih; Budi Rahardjo; Bandul Suratmo (AGRICOLA, 2012)
One of efforts of food diversification is used flour from tubers as a supplement or substitution for wheat flour. Sweet potatoes are one of another.  The sweet potato tuber was change become different form as chips before drying then crushed it into flour. The drying process generally occurs in three periods. At the first time is pre- heating, constant rate periods in the second, and the last time is falling rate periods. Between constant and falling rate periods, there is critical moisture content point (Mk). At this point there is not enough water on the surface to maintain a water activity value of one.  Moisture content decrease very slowly at falling rate periods and require a long time to achieve moisture content we need (about 7% wb for wheat flour). Dried chips ready for flouring when the critical moisture content (Mk) was reached. The changing become smaller particles as flour aims to accelerate the drying process, so the amount of heat energy we used can be suppressed. The determination of critical moisture content (Mk) is reached by mathematical equation approach. Mathematical equations made from a constant during falling rate and constant rate periods. This mathematical equation is derived from observation of the material moisture content.  The experiment was made of different thickness of chips and two cultivars of sweet potato which were yellow tuber and purple one. The result is lower critical moisture content at the thicker chips. Drying time is related with amount of heat energy that used to evaporate the water from material. The best time to drying at the purple sweet potato is moisture content to 36% wb and thickness of chips 4 mm. For the purple, the best time to drying is also at moisture content to 36% wb and thickness of chips 1 mm.